Pengembangan bahan ajar sub konsep sistem endokrin pada manusia untuk peserta didik sekolah menengah atas fase F berbentuk e-booklet - Royani, Syafarina; Noorhidayati, Noorhidayati; Nurtamara, Luthfiana (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Difficulties in the learning and teaching process of endocrine system material that is considered difficult by students can be assisted by teaching materials in the form of E-Booklets to facilitate students in understanding the concept of the endocrine system. The purpose of the study was to develop an endocrine system E-Booklet using Thiagarajan's 4D model which is carried out in 4 stages, namely, 1) Define, namely analyzing and identifying problems to obtain various information related to the product being developed, 2) Design, which is designing a development that can be used in learning, 3) Develop, which is an assessment by validators carried out by testing suitability and feasibility, and 4) Disseminate, which is disseminating limitedly to test schools and will be carried out scientific publications. The data collection technique used questionnaire instruments for suitability, feasibility, and readability. The research subjects were 3 validators and 12 good participants. The test results of the Endocrine System E-Booklet in Humans showed: 1) The suitability test results have a very suitable category (4.39) which means that the E-Booklet is very suitable for learning objectives, media, format, and language; 2) The feasibility test results have a very feasible category (4.49) which means that the E-Booklet in use is very feasible to use as a biology teaching material; 3) The readability test results have a very good category (4.49) which means that it is very well understood by students. Based on the results of the development test, the E-Booklet of the endocrine system has been obtained in the category of very suitable, very feasible, and very good so that it can be used by students and teachers in the biology learning process.Kesulitan dalam proses belajar dan mengajar materi sistem endokrin yang dianggap sulit oleh peserta didik dapat dibantu dengan bahan ajar berbentuk E-Booklet untuk memudahkan peserta didik dalam memahami konsep sistem endokrin. Tujuan penelitian adalah mengembangkan E-Booklet sistem endokrin menggunakan model 4D Thiagarajan yang dilakukan dalam 4 tahapan yaitu, 1) Define, yaitu menganalisis dan mengidentifikasi masalah untuk memperoleh berbagai informasi yang berkaitan dengan produk yang dikembangkan, 2) Design, yaitu merancang suatu pengembangan yang dapat digunakan dalam pembelajaran, 3) Develop, yaitu penilaian oleh validator dilakukan dengan menguji kesesuaian dan kelayakan, dan 4) Disseminate, yaitu menyebarluaskan secara terbatas pada sekolah uji dan akan dilakukan publikasi ilmiah. Teknik pengumpulan data menggunakan instrumen angket kesesuaian, kelayakan, dan keterbacaan. Subjek penelitian adalah 3 validator dan 12 peserta baik. Hasil pengujian E-Booklet Sistem Endokrin Pada Manusia menunjukkan: 1) Hasil uji kesesuaian memiliki kategori sangat sesuai (4,39) yang berarti E-Booklet sangat sesuai dengan tujuan pembelajaran, media, format, dan bahasa; 2) Hasil uji kelayakan memiliki kategori sangat layak (4,49) yang berarti E-Booklet secara penggunaan sangat layak digunakan sebagai bahan ajar biologi; 3) Hasil uji keterbacaan memiliki kategori sangat baik (4,49) yang berarti sangat baik dipahami oleh peserta didik. Berdasarkan hasil uji pengembangan telah diperoleh E-Booklet sistem endokrin dalam kategori sangat sesuai, sangat layak, dan sangat baik sehingga dapat digunakan oleh peserta didik dan guru dalam proses pembelajaran biologi.